Sou Repórter Correio: as motivações do público para atuar na coprodução do Jornal da Correio - Nascimento, Gilmara Dias do (2022)
After 18 years inside a newsroom, it is inevitable to notice the changes that journalism has gone through. One of them was the role of the citizen within the process of building both the news itself and the news. This research investigates the motivations that lead citizens to produce videos for the news program Jornal da Correio (TV Correio, affiliate Record TV in Paraíba) through the frame “Sou Repórter Correio”, as well as their perceptions after broadcasting. To achieve this objective, as a theoretical framework we discuss different concepts that involve public participation in television news. As a method, we conducted semi-structured interviews with 10 coproducers, who participated in the frame by sending videos. In addition, participant observation was also carried out in the newsroom of Jornal da Correio to understand the reception aspects and the productive routines applied to the use of these videos. Based on the results achieved, our study helped to deepen knowledge about what motivates the public to participate, indicating that the belief that television shortens paths between the population and public authorities so that collective problems can be solved. This is a great motivating factor that brings co-producers closer to the field of journalism as well as professionals to co-producers.